Rhizopus oryzae AM16; a new hyperactive L‑asparaginase producer: Semi solid‑state production and anticancer activity of the partially purified protein. Issue 3 (2022) - OTHMAN, SARAH I.; MEKAWEY, AMAL A.I.; EL‑METWALLY, MOHAMMAD M.; GABR, SAMI A.; ALWAELE, MAHA ABDULLA
No abstract available